Campo-ciudad: enigma, política y verdad de puestas en escena del ballet Estancia de Alberto Ginastera - Mariana Signorelli (telondefondo. Revista de Teoría y Crítica Teatral, 2013)
This article focuses on the dichotomy countryside/city as a thematically and aesthetically recurrent idea in the different stagings of Alberto Ginastera’s ballet Estancia.